Glycomics-based serum markers as reliable tool for assessment of viral response after treatment with direct-acting antiviral drugs in hepatitis C virus infection. Issue 2 (4th March 2023) - Somers, Nicky; Vandekerckhove, Elisabeth; Geerts, Anja; Degroote, Helena; Lefere, Sander; Devisscher, Lindsey; Meuris, Leander; Callewaert, Nico; Van Vlierberghe, Hans; Verhelst, Xavier
ABSTRACT: Objectives: Patients with chronic hepatitis C virus (HCV) infection have a genuine risk of developing liver fibrosis and cirrhosis, potentially resulting in hepatocellular carcinoma (HCC), a risk that remains even after sustained viral response (SVR). Glycomics-based biomarkers are an attractive tool to closely monitor these patients during and after antiviral treatment, as alterations in the abundance of N-glycans reflect an altered state of the liver. This study assessed serum glycomics for the evaluation of inflammation-related fibrosis regression during and after treatment of HCV with DAAs. Methods: The GlycoFibroTest and GlycoCirrhoTest were analyzed in the sera 36 HCV-infected patients with advanced fibrosis (F3) or established cirrhosis (F4), before (week 0), during (week 12) and after (week 24) a twelve-week oral administration of DAAs therapy – using an optimized glycomic technology on a DNA sequencer. Results: All patients achieved SVR after treatment and two of them developed HCC in the subsequent five years. A significant decrease of the GlycoFibroTest (p < 0.0001) was seen after 12 weeks, consistent with other measured biomarkers (APRI, FIB-4, FibroTest). Statistical analysis was performed in IBM SPSS Statistics version 28.0, using the non-parametric Friedman's test with a statistical significance α level of 0.05. Conclusion: This study suggests that the GlycoFibroTest is a serum biomarker for viral response in HCV patients. The rapid decrease of the glycomics-based biomarker probably reflects the amelioration of liver inflammation as underlying process, rather than the improvement of liver fibrosis itself.